Paediatric registrar's views on current child protection training and willingness to undertake child protection work in the current climate: what needs to be done?. (4th April 2011) - Zalkin, M D; Fertleman, C; Hodes, D
Abstract : Aims: Difficulties surrounding child protection have led to fear and disengagement of paediatricians. We aimed to explore registrar's experiences of child protection work and training, views of their future role and to identify influencing factors. Methods: A questionnaire survey of all paediatric registrars in the North and South London deanery (n=600) and five focus groups of three-four paediatric registrars (n=17). Results: Overall response rate was 33.8% (n=204). Trainees find all areas of child protection consultations more difficult than non-emergency paediatric consultations. 51.5% rated training worse than other areas of paediatrics. 32.6% think they will not be able to do this work confidently and competently as a consultant although 46.4% will view it as part of their future everyday work. Experiential training and case based teaching are most valued. Only 22% find E-learning useful. Rota restrictions, cost and study leave problems make training difficult to access. Many registrars feel isolated, poorly supervised and unsupported by consultants. Over 50% would be more likely to undertake this work in the future if support and training were improved. Other major influencing themes include media reporting, fear of the General Medical Council, and court attendance. 96.4% think there should be 'specialists' in this area. 27.5% expressed interest in such posts and 13.7% would consider being named or designated doctor. Only 14.6% would know how to develop a special interest in this area. Conclusions: Child protection is still not viewed as a necessary and everyday part of paediatrics by all registrars however there are a significant minority with an interest and we have identified important modifiable factors which would attract more trainees. Similar research into consultants is needed to identify how best to support them so they are better able to support trainees. Despite the development of some child protection training by the RCPCH, training for all grades needs to be improved with a clear, structured, mandatory and accessible and training programme starting at undergraduate level and continuing indefinitely. There should also be a formalised training route for development of the 'expert' and the implementation of shorter special interest posts to satisfy the demand that exists among registrars.